INCREASING THE CONTRIBUTION OF GFRP BARS ON THE COMPRESSIVE STRENGTH OF CONCRETE COLUMNS WITH CIRCULAR CROSS SECTION - Tabkhi Wayghan, Amir Reza; Mofid, Massood; Babaei Ravandi, Behnam; Zinati Yazdi, Seyed Morteza (Civil Engineering Journal, 2019)
Corrosion of steel in concrete elements is a major issue in concrete structures. In order to overcome this matter, Glass Fiber Reinforced Polymer (GFRP) reinforcement is being used in concrete members from almost 20 years ago. Although it has been used and developed in recent years, there are still some uncertainties for the application of FRP reinforcement, especially in concrete columns.  Most codes such as ACI, CSA, JSCE & etc. neglects the effect of these reinforcements or they do not permit them in compressive concrete elements. In this essay, it has been shown that these rebar can contribute significantly in compressive strength of concrete columns if the column confinement is provided sufficiently. In order to achieve the required confinement to reach a sharp contribution of GFRP longitudinal rebar in concrete columns, the spiral of FRP rebar with small pitches around longitudinal rebar is taken into account. This leads to higher strains of concrete which can result in a higher contribution of FRP longitudinal rebar. Foremost, equations related to the compressive strength of concrete columns considering the influence of spiral confinement will be carried out. Then, a parametric study will be performed, and the effects of pitch, concrete strength, column diameter, the quantity of longitudinal rebar and concrete cover will be investigated.